2010
DOI: 10.1177/0883073809344621
|View full text |Cite
|
Sign up to set email alerts
|

Upper Extremity Function and Occupational Performance in Children With Spastic Cerebral Palsy Following Lower Extremity Botulinum Toxin Injections

Abstract: We studied the effect of botulinum toxin A injections to the lower extremities of spastic cerebral palsy children on upper limb body function and occupational performance. A total of 16 children with spastic cerebral palsy, aged 2 to 8 years, Gross Motor Function Classification System levels I-IV, referred to a child neurology outpatient clinic for botulinum toxin A injections to the lower limbs, underwent 4 assessments: 1 month prior to injection, immediate pre injection, and at 1 and 5 to 6 months post injec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…25 However, there is a paucity of evidence demonstrating large changes in upper-extremity function after interventions specific to the lower-extremities (i.e. Thus, we do not know the frequency of upper-extremity activities children in the LIFT-control group performed outside of the training.…”
Section: Limitations and Future Considerationsmentioning
confidence: 97%
See 1 more Smart Citation
“…25 However, there is a paucity of evidence demonstrating large changes in upper-extremity function after interventions specific to the lower-extremities (i.e. Thus, we do not know the frequency of upper-extremity activities children in the LIFT-control group performed outside of the training.…”
Section: Limitations and Future Considerationsmentioning
confidence: 97%
“…There is also evidence to suggest that cross-contamination could arise from the transfer of effects from a lower-limb intervention to upper-limb intervention. 25 However, there is a paucity of evidence demonstrating large changes in upper-extremity function after interventions specific to the lower-extremities (i.e. therapy other than botulinum neurotoxin).…”
Section: Limitations and Future Considerationsmentioning
confidence: 99%
“…Furthermore, these bilateral tasks did not allow the child to rest an arm on the table for support, which suggests that the association between gross motor function and upper limb function may be partly related to core stability. For example, a previous study in children with spastic cerebral palsy showed that a botulinum neurotoxin injection to the lower limbs resulted in improved upper limb motor function, including functional ability in daily activities related to self‐care . As discussed by the authors, reduced lower limb spasticity after the injection may have allowed for more effective muscle recruitment, including stabilization of the pelvis and postural control of the trunk.…”
Section: Discussionmentioning
confidence: 96%
“…For example, a previous study in children with spastic cerebral palsy showed that a botulinum neurotoxin injection to the lower limbs resulted in improved upper limb motor function, including functional ability in daily activities related to self-care. 18 As discussed by the authors, 18 reduced lower limb spasticity after the injection may have allowed for more effective muscle recruitment, including stabilization of the pelvis and postural control of the trunk. In a similar way, the extent of lower limb involvement and relative core stability may have influenced upper limb motor performance among the current participants, and therefore may partly explain the low scores among those in GMFCS level III.…”
Section: Upper Limb Function and Daily Activitiesmentioning
confidence: 99%
“…A more recent study that used DAbS to compare the ED 50 of different BoNTAs showed that a DAbS of 2 could be obtained with 6 U of onabotulinumtoxinA and 10 U of incobotulinumtoxinA (Brown et al, 2013). Overall, onabotulinumtoxinA showed greater efficacy and longer effect duration than incobotulinumtoxinA at both high and low dosages in the DAbS model (Brown et al, 2013 (Marion et al, 1995) 1: 3 NA (Nussgens and Roggenkamper, 1997;Roggenkamper et al, 2006) 1: 4 AbobA>OnabA (Sampaio et al, 1997) 1: 4 AbobA>OnabA (Bihari, 2005) 1: 4 -1: 5 NA (Bentivoglio et al, 2012) 1: 1 -1: 13.3 NA (Dodel et al, 1997) 1:4 -1:6 AbobA>OnabA Cervical dystonia (Naumann et al, 2003) 1: 5 -1: 6 AbobA=OnabA (Odergren et al, 1998) 1: 3 AbobA=OnabA (Ranoux et al, 2002) 1: 3 -1: 4 AbobA>OnabA (Bihari, 2005) 1: 4 -1: 5 NA (Misra et al, 2012) 3.1: 1 AbobA>OnabA (Rystedt et al 2015) 1.7: 1 NA (Yun et al 2015) 2.5: 1 AbobA=OnabA (Dodel et al, 1997) 1:4 -1:6 AbobA>OnabA (Van den Bergh and Lison, 1998) 1: 2.5 AbobA=OnabA Hemifacial spasm (Marion et al, 1995) 1: 3 NA (Bihari, 2005) 1: 4 -1: 5 NA (Dodel et al, 1997) 1:4 -1:6 AbobA>OnabA (Van den Bergh and Lison, 1998) 1: 2.5 AbobA=OnabA Spasticity (Rasmussen, 2000) 1: 4 NA (Bhakta et al, 1996) 1: 4 -1: 5 NA (Hesse et al, 2012) 1: 5 NA ( Keren-Capelovitch, et al 2010) 1: 2.5 NA Abbreviations: OnabA =OnabotulinumtoxinA; AbobA=AbobotulinumtoxinA; NA=not available/not applicable © C I C E d i z i o n i I n t e r n a z i o n a l i at least 12 months, were administered increasing doses of onabotulinumtoxinA until a similar response to that obtained with abobotulinumtoxinA was observed. The dose ratio between onabotulinumtoxinA and abobotulinumtoxinA was 1:3 (Marion et al, 1995).…”
Section: Pharmacological Safetymentioning
confidence: 99%